UV-lnduced Transformations of 3-Chloro-4-methoxy-benzaldehyde in Low-Temperature Matrices - Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2019)
Halogen- and methoxy-substituted benzaldehydes are relevant compounds in various fields, from fragrance industry to agrochemicals or drugs manufacturing [1,2], In the present study, 3-chloro-4-methoxy-benzaldehyde (3CMBA; see Figure), which is a representative molecule of the mixed halogen/methoxy-substituted benzaldehyde family of compounds, has been investigated by matrix isolation infrared spectroscopy and Density Functional Theory calculations. Molecules of the compound were isolated in cryogenic argon and xenon matrices (15-30 K) and the conformational composition of the as-deposited materials characterized by infrared spectroscopy. Two conformers differing in the orientation of the aldehyde group relatively to the chlorine ring substituent were efficiently trapped in the matrices from the gas phase, with the cis conformer (represented in the Figure) being slightly higher in energy than the trans form (fSEIpis-trans} = 0.22 kJ mol"1; AG°(cis-trans) = 0.41 kJ mol"1). Both these conformers have the methoxy group pointing to the opposite direction of the chorine atom. Two additional higher-energy forms, with energies higher than the conformational ground state by about 15 kJ mol"1, were also predicted by the calculations, but their expected populations are negligible and are of no practical importance. The orientation of the methoxy group in these higher-energy conformers is approximately perpendicular to the aromatic ring. The as-deposited matrices of 3CMBA were irradiated by tunable monochromatic UV-light provided by a Laser/MOPO system in the UV range. Irradiation at 299 nm was found to induce conversion of the cis into the trans conformer, while irradiation at 296 nm induces the reverse photoisomerization. Irradiation at higher energy (250 nm) was found to lead to decarbonylation of both conformers with production of CO and 2-chloro-methoxy-benzene. Very interestingly, the observed UV-induced processes were found to take place in an essentially selectively way as a function of the irradiation wavelength. In particular, the conformational isomerizations occur with only a residual number of molecules undergoing simultaneous decarbonylation.